An Ethnochoreological Analysis of Historical Transformation and Socio-Ecological Critique of SANG Dance in Belitung - Muhammad Akbar Lazuardi Suherman; Beben Barnas; Tatang Taryana (Gondang: Jurnal Seni dan Budaya, 2026)
This study analyzes the expressive, symbolic, and communicative functions of movement in SANG Dance from Belitung Island through an ethnocoreological framework. SANG Dance, created by Bella Asmanabillah, uses pepper (sahang) as its central symbol to narrate the historical transformation of Belitung society across three choreographic phases: imbang (pre-colonial), ambang (colonial), and rumpang (post-colonial). This qualitative descriptive research collected data through in-depth interviews, participatory and non-participatory observation, and documentation involving the choreographer, dancers, arts observers, and the supporting community. Data were analyzed using the Miles and Huberman interactive model, and validity was strengthened through source and method triangulation. Results show that movement in SANG Dance functions expressively to convey the collective experience of Belitung people, symbolically to represent the relationship between humans and nature, and communicatively to deliver social criticism regarding ecological exploitation and cultural identity loss. The choreographic structure reflects the historical transformation of Belitung society from harmonious agrarian life, through exploitative colonial systems, to the post-colonial condition marked by social fragmentation and environmental degradation. SANG Dance thus serves not merely as an aesthetic expression but as a medium of social critique, cultural preservation, and ecological consciousness. This study contributes to ethnocoreology by positioning choreography as a cultural text that encodes collective memory, local identity, and socio-ecological criticism rooted in local commodity history.